(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
New types of fertilizers based on peat and sapropel were developed and can be used as solid and liquid forms of organic and organicmineral fertilizers and preparations for different crop cultivation. It was shown that use of SAPROAgro and SAPROЕlixir fertilizers increases productivity of agricultural plants by 9-16 %. Use of EleGum liquid humic microelement fertilizers provides an increase of winter wheat grain yield up to 0.88 t ha-1 , maize green mass up to 5.0 t ha-1 and maize grain to 2.06 t ha-1